Can a Glove-Coach Technology Significantly Increase the Efficacy of Cardiopulmonary Resuscitation on Non-healthcare Professionals? A Controlled Trial - Musiari, Michele; Saporito, Andrea; Ceruti, Samuele; Biggiogero, Maira; Iattoni, Martina; Glotta, Andrea; Cantini, Laura; Capdevila, Xavier; Cassina, Tiziano (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Cardiovascular accidents are the world’s leading cause of death. A good quality cardiopulmonary resuscitation (CPR) can reduce cardiac arrest-associated mortality. This study aims to test the coaching system of a wearable glove, providing instructions during out-of-hospital CPR. Materials and Methods: We performed a single blind, controlled trial to test non-healthcare professionals during a simulated CPR performed on an electronic mannequin. The no-glove group was the control. Primary outcome was to compare the accuracy of depth and frequency of two simulated CPR sessions. Secondary outcomes were to compare the decay of CPR performance and the percentage of duration of accurate CPR. Results: 600 chest compression were performed, 571 chest compressions were analyzed. Mean frequency in the glove group was 117.67 versus 103.02 rpm in the control group (p<0.001). Appropriate rate cycle was 92.4% in the glove group vs 71% in control group, with a difference of 21.4% (p<0.001). Mean compression depth in the glove group was 52.11 versus 55.17 mm in the control group (p<0.001). A mean reduction of compressions depth over time of 5.3 mm was observed in the control group versus 0.83 mm of reduction in the glove group. Conclusion: Visual and acoustic feedbacks provided through the utilization of the glove’s coaching system were useful for non-healthcare professionals’ CPR performance.